The relationship between organizational justice and organizational citizenship among the workers. A field study in the unit of research on renewable energies in the desert center in Adrar Algeria - Al Dahbi, Hayat Ibrahim; Boukmeish, Ali Mohammed Al Shareef (Journal of Humanities & Social Sciences, 2019)
The purpose of this study is to examine the relationship between Organizational Justice and Organizational Citizenship behavior among workers in the Algerian Institution. By Knowing the level of presence both variables, and the impact of Organizational Justice on Organizational Citizenship behavior in the Algerian institution.The Study relied on the a descriptive approach and it used the Questionnaire to collect data from the field of study represented in the Renewable Energy Research Unit in Saharan Medium, by using a comprehensive Survey of workers totaling 74 workers.The most important results found by this study:The low level of distributive justice, procedural fairness, and procedural justice in the Algerian establishment does not lead to a decrease in the level of organizational citizenship practiced by its workers. As well as a negative relationship between organizational justice and organizational citizenship behavior.
Keywords: organizational justice; distributive justice; procedural justice; Transactional justice organizational citizenship behavior